Establecer el protocolo para la Técnica de Colangioresonancia Magnética en el Hospital Sociedad de Lucha contra el Cáncer (SOLCA Núcleo de Loja) periodo enero - mayo del 2013. - Cahueñas Cuenca, Isamar Stephanie (2013)
The magnetic colangioresonancia (CRM) is a relatively new technique, first described in 1991 a noninvasive method that permits evaluation of the biliary tract, is a noninvasive imaging technique that has demonstrated a high diagnostic accuracy irrespective of the various pathologies of the biliary   This present thesis work was carried out with the aim of Set the Protocol to The Magnetic Colangioresonancia Technique In The Hospital Company In Fight Against Cancer (CORE SOLCA Loja), for which it has been sampled 35 clinical cases for embodiment thereof, during the period from January to March of 2013, leading to results that in 40% of these cases are done for a chronic cholecystitis, followed by 34% for acute cholecystitis and the lowest percentages between 14% and 12% incidences have colecistosis dyskinesias and between the ages of 50 to 60 years old. The methodology was qualitative and descriptive method for characterization; research and development of every single detail for the specification in a practical and descriptive of the important properties of the characteristics of Magnetic Colangioresonancia Technique in the Diagnosis of the various pathologies the biliary tree. In conclusion, the CRM has a high sensitivity and specificity, positive predictive value 91% and negative 97%, which will assess by 99.99% pathologic segments of the biliary tree, demonstrates a high diagnostic power. We recommend placing a coil antenna or Body Array, which will allow better spatial resolution imaging, verify urea and creatinine tests to proceed with the examination of CRM and use in a mouthful of water with 1.5 to 2 cc of cons of gadolinium, for displaying detailed form of the bile ducts and gastric chamber, this should be done prior to entering the patient to the resonator   DESCRIPTION OR TAGS: Fat Saturation Factor (FAST), 2D and 3D Acquisition, FID (free induction decay), Repetition Time (TR), Colangioresonancia, Pager. Catenuacion Biliary tract. DEGREE TO GET: Technologist in Radiology and Diagnostic Image. ACADEMIC AREA: Area Human Health. CAREER: Diagnostic Radiology Image.